The KUMEMEJIMA 2009 Expedition: station data and collecting sites - Naruse, Tohru (Zootaxa, 2012)
The present paper introduces the sampling methods employed during the Marine Biodiversity Expedition — KUMEJIMA 2009. Data of all sampling stations are listed.